(3eNJUQ aj GdMSGHs - (3GdYWGQ , eMeO GdYWGQ GdOeTbj,J (B1234 (3g` s
(3ChdgG (B:s
(3bGd QVi Gddg Yfg hCQVGg EYde habc Gddg deQGVjg Cf GdMSGH KdGKI eQGJH s
(3BNQgG (B:s
(3hef SJjf MHI hgPG LejY ceG TQWfG PcQg gPG GdeNJUQ hGdMeO ddg Ydi fYeg GdXGgQI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdMGOjI YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B295s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs